An economic model of social sensitivity: The case of individual criminal behavior - Buck, Andrew Jepherson (Journal of quantitative criminology, 1989)
In general, economists have modeled criminal behavior as a problem in time allocation under uncertainty. Their Friedman-Savage utility models have been based on the binomial probability distribution and then tested using aggregate data on crime rates and neglect the nonpecuniary aspects of crime. This paper overcomes the shortcomings of previous work. Specifically, criminal activity is modeled with an underlying geometric probability process and explicitly accounts for the moral and social compromise involved in becoming a criminal. The empirical model enables the quantification of the criminal's moral and social sensitivity using data based on a consolidated file of police records and a cohort survey of criminals and noncriminals. On the basis of this unique data set, it is found that the included individual criminals are risk averse and that gang membership reduces social sensitivity.